Analyzing the determinants of cash holdings of small and medium-sized entities in Nigeria - Tsagem, Muhammad Musa; Aripin, Norhani; Ishak, Rokiah (2015)
Purpose: This paper aims to report the results of an empirical investigation on the determinants of the cash holdings for small and medium-sized entities. The paper considers the different explanatory factors of SMEs cash holdings for a sample of Nigerian SMEs. SMEs are springboard of the Nigerian economy contributing to gross domestic product, employment generation and industrialization.Methodology: the study employed panel data regression analysis using secondary data on a sample of 311 Nigerian SMEs for the period 2007 - 2013.Result: The finding which is robust of endogeneity shows statistically significant association between cash conversion cycle, account receivables period, return on assets and board size with SMEs cash holdings. Also found a significant relationship between cash holdings with firm size, leverage, growth opportunities and firm age. Implication: Thus, the result of the study indicates that Nigerian SMEs with shorter cash conversion cycle and low growth opportunities hold more cash. Similarly, SMEs with small board of directors accumulate large cash balance. Further, SMEs with higher profitability keep large cash balance. This study contributes to existing literature on the determinants of SMEs cash holdings more specifically in developing economies. However, this study is limited to non-financial and non-service SMEs. Future study should extend the investigation to financial and services firms. Similarly the structure of the paper and scope of further study may be extended to include the effects of more corporate governance mechanisms.